Examining the visual effect of trypophobic repetitive pattern in contemporary urban environments: Bahrain as a case for middle east countries - Alkhalifa, Fay; Wilkins, Arnold; Almurbati, Nehal; Pinelo, Joao (Journal of Architecture and Urbanism, 2020)
New building materials and design technologies such as design parameterisation allow for the creation of unusual architectural elements composed of spatially repetitive patterns. Images with specific spatial properties, as from repetitive patterns, may cause psychological and physiological reactions, in some cases leading to severe discomfort, headaches or seizures. Clusters of roughly circular shapes, often hollow, are also known to create reactions such as sickness and vomiting in certain individuals. The phenomenon is known as trypophobia. Because trypophobia has only recently been described and is not widely recognised, we undertook a survey of the public reaction to trypophobic images, as well as to patterns that are known to have a neurological effect, viz. patterns of stripes. The study investigates whether the two types of pattern are similarly aversive and examines the extent of the aversion to find out whether trypophobia needs to be considered when designing buildings. We showed a variety of images to 405 members of the public to gauge their reaction. In some instances, the reaction was profound: one person vomited. The findings suggest that reactions to stimuli in the built environment are significant enough to provoke a debate on the role of visual discomfort in architecture and sustainable urbanism. It seems important to further investigate the properties of architectural shapes that induce discomfort so as to avoid a public health concern in contemporary urban environments.